2014
DOI: 10.1038/nrgastro.2014.27
|View full text |Cite
|
Sign up to set email alerts
|

Advances in IBD genetics

Abstract: IBD is a spectrum of chronic disorders that constitute an important health problem worldwide. The hunt for genetic determinants of disease onset and course has culminated in the Immunochip project, which has identified >160 loci containing IBD susceptibility genes. In this Review, we highlight how genetic association studies have informed our understanding of the pathogenesis of IBD by focusing research efforts on key pathways involved in innate immunity, autophagy, lymphocyte differentiation and chemotaxis. S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
76
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 121 publications
(76 citation statements)
references
References 208 publications
0
76
0
Order By: Relevance
“…Currently, the paradigm proposed is a feed-forward synergistic dysregulation of the mucosal epithelial barrier, the mucosal immune system, and gut microbiota (2,6,52). Metagenomic and genome-wide association studies have clearly confirmed the role of all three in the progression of IBD (12, 20, 24, 35, 46, 50a, 52).…”
mentioning
confidence: 98%
“…Currently, the paradigm proposed is a feed-forward synergistic dysregulation of the mucosal epithelial barrier, the mucosal immune system, and gut microbiota (2,6,52). Metagenomic and genome-wide association studies have clearly confirmed the role of all three in the progression of IBD (12, 20, 24, 35, 46, 50a, 52).…”
mentioning
confidence: 98%
“…Indeed, polymorphisms in multiple members of the NOD-like receptor family of intracellular pattern recognition receptors are associated with various inflammatory diseases (2,3). The NOD-like receptor family member NOD2 is one of best characterized genetic risk factors in the pathogenesis of Crohn disease (CD) 3 (4,5). NOD2, which is expressed in a variety of cell types, including intestinal epithelial cells, macrophages, and dendritic cells, functions as a sensor for bacterial peptidoglycan (6,7).…”
mentioning
confidence: 99%
“…A specific association of NKX2-3 rs1088365 with smoking CD patients has been observed (310 CD and 976 controls) (van der Heide et al, 2010). These studies have been reviewed (Cho and Brant, 2011;Van Limbergen et al, 2014).…”
Section: Inflammatory Bowel Disease (Ibd)mentioning
confidence: 99%